PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK KELAS VIII SMP NEGERI 10 PADANG - Nurul Indah Aini (Departemen Matematika, 2019)
Understandingof mathematical concepts ability is one of the basic capabilities that should be owned by everylearners in the learning of mathematics. However, the 8th grade of mathematics in Junior High School 10 Padang, students mathematical conceptsability was not optimal yet. It was becausethe learning process wasstill teacher-centered. To overcome this, teacher neededto apply the learning model to facilitatethe students for understanding of mathematical conceptsto improve their own knowledge. The learning model that could be usedCooperative Learning type Think Talk Write (TTW). This kind of research was quasi experiment, with Static Group Design. Based on the results of data analysis is using t-test, it is obtained P-value=0,023 < α=0.05, so it can be concluded that the ability of the understanding of mathematical concepts of students who studies with Cooperative Learning type TTW is better than those who learns with conventional learning. Keywords–conventional learning, cooperative learning,mathematical concepts , think talk write